Mitochondrial genome diversity of Balamuthia mandrillaris revealed by a fatal case of granulomatous amoebic encephalitis - Law, Cherie Tsz-Yiu; Nivesvivat, Thirapa; Xiong, Qing; Kulkeaw, Kasem; Shi, Ling; Ruenchit, Pichet; Suwanpakdee, Detchvijitr; Suwanpakdee, Piradee; Tongkrajang, Nongnat; Sarasombath, Patsharaporn T.; Tsui, Stephen Kwok-Wing (Frontiers in Microbiology, 2023)
Balamuthia (B.) mandrillaris is a free-living amoeba that can cause rare yet fatal granulomatous amoebic encephalitis (GAE). However, efficacious treatment for GAE is currently unavailable especially when genomic studies on B. mandrillaris are limited. In this study, B. mandrillaris strain KM-20 was isolated from the brain tissue of a GAE patient and its mitochondrial genome was de novo assembled using high-coverage Nanopore long reads and Illumina short reads. Phylogenetic and comparative analyses revealed a range of diversification in the mitochondrial genome of KM-20 and nine other B. mandrillaris strains. According to the mitochondrial genome alignment, one of the most variable regions was observed in the ribosomal protein S3 (rps3), which was caused by an array of novel protein tandem repeats. The repeating units in the rps3 protein tandem region present significant copy number variations (CNVs) among B. mandrillaris strains and suggest KM-20 as the most divergent strain for its highly variable sequence and highest copy number in rps3. Moreover, mitochondrial heteroplasmy was observed in strain V039 and two genotypes of rps3 are caused by the CNVs in the tandem repeats. Taken together, the copy-number and sequence variations of the protein tandem repeats enable rps3 to be a perfect target for clinical genotyping assay for B. mandrillaris. The mitochondrial genome diversity of B. mandrillaris paves the way to investigate the phylogeny and diversification of pathogenic amoebae.